Asuwish - Noho, Noranierah; Sabli, Nor Azieamirah; Esmadi, Nur Alia Azrin; Bujang Uti, Tiana; Mohd Yusof, Nur Fahzira (2016)
Nowadays, crimes often happen even in a place or a time that we can't even predict. Therefore, we open a company named ' AsUWish'. This business is provided for public, students and working person. As this company form as a partnership, it shared by five members. This company manage by Noranierah Binti Noho as a General Manager, while Nor Azieamirah binti Sabli as an Administration Manager, Tiana Binti Bujang Uti as a Marketing Manager,Nur Alia Azrin binti Esmadi as an Operational Manager, and Nur Fahzira binti Yusof as a Financial Manager. This company is set up at One Borneo Hypermall, Kota Kinabalu. Without a doubt, the safety alarm system industry is expanding nowadays. The market is huge because current issues that happen in our country. This product was inspired by these current issues. It is a powerful marketing tool to improve the security system where Malaysia is known as a developing country that has its own mission to become a highly develop country at year 2020. Therefore, we aid our country to achieve this mission. Because of the booming of safety alarm system industry, our company will be able to get support from the supplier. The supplier will be really interested in investing in is when they see an opportunity to support and expand this product out there since they will gain profit. The credit term that the suppliers will offer in term of payment is by fixed payment.